Marine Evidence for GIS Stability and History of Jakobshavn Isbrae, West Greenland, from the LGM to Holocene - Anne Jennings (Arctic Data Center, 2014)
Intellectual Merit: The Principal Investigators will reconstruct the Late Quaternary-Holocene behavior of Jakobshavns Isbrae (JAKIB) in western Greenland, one of the largest ice streams draining the modern Greenland Ice Sheet (GIS). The period from the Last Glacial Maximum (LGM) to the present will be studied because it involves the most recent large scale change in the mass-balance of the ice sheet, it is the period that will be best preserved in continental shelf sediments, and it is the period for which the highest resolution proxy records of paleo-climate from the Greenland ice cores are available. Given the scale of this ice stream and the size of its associated drainage basin, the investigation will provide information on the Late-Quaternary-Holocene behavior and stability of a major area of the GIS. This research will allow assessment of the links between deglaciation and internal and external environmental controls, such as the influence of inflowing Atlantic Water, and will facilitate modeling of the likely future behavior of the GIS. The Principal Investigators will participate in a research cruise of the British Research Vessel, Sir James Clark Ross, to West Greenland in the late summer of 2007 and collaborate with British colleagues on the post-cruise, interdisciplinary program of laboratory work and modeling. Well-dated, high-resolution sediment records from a transect of sites extending from the shelf edge and along the shelf trough, to sites within Disko Bugt both proximal and distal to the modern ice margin will be acquired on the basis of geophysical data. The hypotheses to test using these cores are: Hypothesis 1: Glacier ice extent and interactions between the West Greenland Current and the GIS are recorded in the foraminiferal faunas, mineralogical variations, and Sm and Nd isotopic compositions of the sediments. Hypothesis 2: The West Greenland Current has changed in strength, flowpath and watermass composition from the LGM through the Holocene. These variations have played and continue to play a key role in ice-sheet behavior. Broader Impacts: The underlying rationale for this research is to determine if recent (last ~ 100 yr) observed changes to the mass balance of the GIS reflect natural variability in ice sheet dynamics, or if they relate to anthropogenically-induced climate warming. Key to resolving this is an understanding of ice sheet behavior since the LGM and including periods in the past near Greenland that were as warm or, even warmer than today, such as the middle Holocene optimum. This research will make new discoveries concerning the timing and extent of the Greenland Ice Sheet at the LGM on its western margin, and the behavior of the JAKIB ice stream during deglaciation, new information that will inform paleoceanographers and climate and sea-level modelers. This project is an international effort. It will support a U.S. PhD student, and two undergraduate students. It will involve international student exchanges between the University of Colorado and the United Kingdom. The data acquired will be lodged in the NOAA Paleoclimate Database. CORES: 2008-070CC - 68.228N -57.618W JR175-VC20 - 68.201N -57.756W JR175-VC35 - 67.701N -59.342W